2015
DOI: 10.1021/ie5045007
|View full text |Cite
|
Sign up to set email alerts
|

Basic Ionic Liquid Supported on Mesoporous SBA-15 Silica as an Efficient Heterogeneous Catalyst for Biodiesel Production

Abstract: In the present study, SBA-15 silica-supported basic ionic liquid was prepared through grafting of 4-butyl-1,2,4-triazolium hydroxide onto SBA-15 silica using 3-chloropropyltriethoxysilane as a coupling reagent. The structural properties of the prepared catalysts were investigated by a series of techniques, such as Hammett titration method, elemental analysis, small angle XRD, FT-IR, SEM, TEM, and N2 adsorption–desorption. The characterization results demonstrated that the ionic liquid was successfully tethered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…The textural properties of the samples were calculated from the N 2 adsorption-desorption isotherms at 196 , as listed in Table 2. For the SBA-15 support, the average pore size was 6.64 nm, and the BET surface area and total pore volume were calculated to be 5.89 m 2 /g and 0.92 cm 3 /g, respectively, which were in accordance with the literature data 34,35 . After immobilization of the guanidine base, as indicated in Table 2, the surface area and pore volume were found to decrease to 263 m 2 /g and 0.52 cm 3 /g, respectively.…”
Section: Catalyst Characterizationsupporting
confidence: 86%
See 1 more Smart Citation
“…The textural properties of the samples were calculated from the N 2 adsorption-desorption isotherms at 196 , as listed in Table 2. For the SBA-15 support, the average pore size was 6.64 nm, and the BET surface area and total pore volume were calculated to be 5.89 m 2 /g and 0.92 cm 3 /g, respectively, which were in accordance with the literature data 34,35 . After immobilization of the guanidine base, as indicated in Table 2, the surface area and pore volume were found to decrease to 263 m 2 /g and 0.52 cm 3 /g, respectively.…”
Section: Catalyst Characterizationsupporting
confidence: 86%
“…Besides, it is interesting to note that the adsorption-desorption hysteresis occurred at a relative pressure of about 0.75 owing to capillary nitrogen condensation, demonstrating that the materials contain mesoporous structure with high-ordering and relatively uniform pore size 34 . For the SBA-15-pr-guanindine catalyst, the capillary condensation appeared to shift toward lower pressures and the amount of adsorbed nitrogen was reduced in comparison with the parent SBA-15 silica.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…[14] Recently,i tw as reported that hydrogen-bond-donor groups such as hydroxyl or carboxyl groups, and cocatalysts with ah ydrogen-bond donor could greatlyi mprove the activity of IL-based catalysts. [18] ILs and IL-based polymers have been supported on mesoporouss ilicas, such as SBA-15 and MCM-41. The heterogenization of ILs onto polymer networks is an efficient way to prepare IL-based solid catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilizing ILs on the solid surface by chemical grafting is an effective way to solve the leaching problem. Xie et al (2015) prepared a SBA-15 silica-supported basic IL through grafting of 4-butyl-1,2,4-triazolium hydroxide onto SBA-15 silica using 3-chloropropyltri ethoxysilane as a coupling reagent. The IL was successfully tethered on the SBA-15 support, and the hexagonally ordered mesoporous structure of SBA-15 silica was well retained even after the chemical grafting reaction.…”
Section: Conversion Of Biomass Into Biofuelsmentioning
confidence: 99%